2015
DOI: 10.1007/s00774-015-0674-2
|View full text |Cite
|
Sign up to set email alerts
|

Gender- and age-group-specific associations between physical performance and bone mineral density, falls, and osteoporotic fractures in Koreans: the Chungju Metabolic Disease Cohort study

Abstract: Several factors increase the risk of fragility fracture, including low bone mineral density, falls, and poor physical performance. The associations among these factors have been investigated; however, most of the subjects of previous studies were either elderly men or elderly women, and the associations were controversial. The aim of this study was to evaluate the associations between physical performance and bone mineral density, and the history of falls and fractures, stratified by gender and age group. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Our database searches identified a total of 4,310 unique records. After the two-stage screening and additional papers identified via the reference list search, a total of 55 papers are included in the review (Andresen et al, 2006;Ansai et al, 2016;Arai et al, 2020;Beauchet et al, 2010;Bergland and Wyller, 2004;Blain et al, 2021;Bongue et al, 2011;Briggs et al, 1989;Buatois et al, 2006;Buatois et al, 2010;Cho and Kamen, 1998;Choy et al, 2008;Choy et al, 2007;Crenshaw et al, 2020;de Rekeneire et al, 2003;Delbaere et al, 2010;Depasquale and Toscano, 2009;Ek et al, 2019a;Ek et al, 2019b;El-Sobkey, 2011;Eto and Miyauchi, 2018;Gerdhem et al, 2005;Hasegawa et al, 2019;Hashidate et al, 2011;Heitmann et al, 1989;Ikegami et al, 2019;Jalali et al, 2015;Kwan et al, 2011;Lim et al, 2016;Lin et al, 2004b;MacRae et al, 1992;Mahoney et al, 2019;Moreira et al, 2017;Muir et al, 2010;Mulasso et al, 2017;Nevitt et al, 1989;Niam and Wee, 1999;Park et al, 2020;Porto et al, 2020;Rossat et al, 2010;…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our database searches identified a total of 4,310 unique records. After the two-stage screening and additional papers identified via the reference list search, a total of 55 papers are included in the review (Andresen et al, 2006;Ansai et al, 2016;Arai et al, 2020;Beauchet et al, 2010;Bergland and Wyller, 2004;Blain et al, 2021;Bongue et al, 2011;Briggs et al, 1989;Buatois et al, 2006;Buatois et al, 2010;Cho and Kamen, 1998;Choy et al, 2008;Choy et al, 2007;Crenshaw et al, 2020;de Rekeneire et al, 2003;Delbaere et al, 2010;Depasquale and Toscano, 2009;Ek et al, 2019a;Ek et al, 2019b;El-Sobkey, 2011;Eto and Miyauchi, 2018;Gerdhem et al, 2005;Hasegawa et al, 2019;Hashidate et al, 2011;Heitmann et al, 1989;Ikegami et al, 2019;Jalali et al, 2015;Kwan et al, 2011;Lim et al, 2016;Lin et al, 2004b;MacRae et al, 1992;Mahoney et al, 2019;Moreira et al, 2017;Muir et al, 2010;Mulasso et al, 2017;Nevitt et al, 1989;Niam and Wee, 1999;Park et al, 2020;Porto et al, 2020;Rossat et al, 2010;…”
Section: Resultsmentioning
confidence: 99%
“…country, sex). For example, only five papers considered sex differences in their analyses (Blain et al, 2021;Ek et al, 2019a;Ek et al, 2019b;Lim et al, 2016;Vellas et al, 1998), despite conceivable sex differences indicated by better one-legged balance in men and greater prevalence of falls in women (Blodgett et al, 2020a;Cooper et al, 2011;Overstall et al, 1977;Peeters et al, 2018;Springer et al, 2007). Similarly, all but one study (Lim et al, 2016) examined associations across the full age range of their sample.…”
Section: Potential Sources Of Heterogeneitymentioning
confidence: 99%
See 1 more Smart Citation
“…Wider age group estimates largely ranged between 20 and 45% for women aged 40 + and 50 + [ 80 – 84 ]. Most estimates for men suggested a prevalence of 15% or lower [ 80 , 85 87 ], although some ranged from 20% to more than 40% for men aged 70 + [ 75 , 77 , 88 ]. The vast majority of fragility fracture incidence data suggested site-specific and combined rates below 500 per 100,000 person-years [ 37 , 38 , 89 91 ], although numerous estimates between 500 and 1000 per 100,000 and even higher were also found, especially for individuals aged 80 + [ 92 97 ].…”
Section: Resultsmentioning
confidence: 99%
“…The ability to stand on one leg over time is a predictor of hip fracture risk [25,26], and several studies have indicated that one-leg stance tests are associated with BMD [21][22][23]. Other physical capability tests, such as the Short Physical Performance Battery (SPPB) and Timed Up and Go (TUG), are often performed when assessing older people's physical capability, to measure the severity of sarcopenia [7] and to evaluate risk of falling [27][28][29]. However, few studies have investigated the association between these tests and BMD.…”
Section: Introductionmentioning
confidence: 99%